Espumas de histórias calcadas na história: "A insólita fortuna" de Luiz Guilherme Santos Neves num jogo dialógico com outras obras desse autor, preenchimento de vazios - Barros, Cláudia Fachetti (2015)
In this work we discuss the possibilities for a dialogue between History of Clio and Literature of Calliope, glimpsed in the works A nau decapitada, As chamas na missa, O templo e a forca and O capitão do fim, Luiz Guilherme Santos Neves. The creative role of literature enters the threshold of its contact with history where the narrative activates the imagination. We will review the look of the fictional author, his writing and insight into the historical moment experienced in Brazil in the narratives studied. Both seek to uncover the world of Clio, the world of suspicion and uncertainty, and, what was once told in a way, can be counted tomorrow another. And in this retelling discuss issues, History, Literature, Historical Fiction and Novel, in which literary and historical texture approach and also depart in a dialogue has been resumed with greater emphasis on contemporaneity.